(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Denitrifying bacteria occur primarily in the soil and play an important role in the nitrogen cycle and wastewater treatment. This study investigated the possibility of isolating denitrifying phototrophic bacteria from marine and aquaculture wastewater. The denitrifying ability of isolates was examined through their utilization of inorganic nitrogen and nitrate reductase test. The photosynthetic capability of the isolates was determined by detecting the photosynthetic pigments (bacteriochlorophyll and carotenoid). Molecular characterization of the isolates was carried out by the amplification of 16S rRNA gene. Forty-five different isolates were obtained and photosynthetic pigments were detected in 12 (8 from marine and 4 from aquaculture). Four of the isolates were found to grow on both inorganic nitrate and nitrite as the sole carbon source. Molecular characterization has shown that the isolates are denitrifying bacteria and the relationship between isolates and other denitrifying bacteria has been established by the construction of the phylogenetic tree. Hence denitrification and denitrifying bacteria can occur in both marine and aquaculture wastewaters.